A home advantage? Examining 100 years of team success in National Hockey League playoff overtime games - McEwan, D. (Psychology of Sport and Exercise, 2019)
Objectives: To examine a potential home (dis)advantage in various types of playoff overtime games in the National Hockey League (NHL). Design: Archival. Method: Success rates for home and away teams in win-imminent overtime games (i.e., wherein a team has an opportunity to win the playoff series) were compared to their respective success in non-imminent overtime games (i.e., the outcome of the game does not determine the outcome of the series). Results: When away teams had an opportunity to win a series, they were significantly more likely to win an overtime game compared to home teams. No such advantage was evident for home teams when they had an opportunity to win a series. Conclusions: When an NHL team has an opportunity to win a playoff series, there appears to be an advantage for visiting teams—not home teams—in winning an overtime game.